Prognostic implications of paradoxical low gradient severe aortic stenosis: a comprehensive analysis from a large multicentric registry. (3rd October 2022) - De Azevedo, D; De Meester, C; Hanet, V; Altes, A; Pouleur, A C; Pasquet, A; Gerber, B; Marechaux, S; Tribouilloy, C; Vanoverschelde, J L; Vancraeynest, D
Abstract: Background: Up to 40% of patients with severe aortic stenosis (SAS; indexed aortic valve area (AVAi) <0.6 cm 2 /m 2 ) present with low transvalvular mean gradient (MG) despite a normal left ventricular ejection fraction (EF). There is intense debate about the prognostic significance of such entity, with some referring to it as an advanced form of the disease, others as an intermediate form between a moderate and a severe form. Objectives: To compare outcome of patients with paradoxical low gradient SAS (PLG-SAS; i.e., mean gradient <40 mmHg and AVAi <0.6 cm 2 /m 2 ) vs. moderate aortic stenosis (MAS; i.e. mean gradient <40 mmHg and AVAi >0.6 cm 2 /m 2 ) and high gradient SAS (HG-SAS; i.e. mean gradient >40 mmHg and AVAi <0.6 cm 2 /m 2 ). Methods: 2582 consecutive patients with aortic stenosis (PLG-SAS, n=933; MAS, n=876 and HG-SAS, n=773) and a preserved EF (>50%) from an international multicentric registry were studied. Five years mortality between groups was compared using Kaplan Meier analysis. Inverse probability weighting was used to adjust for clinical and imaging baseline characteristics. Additionally, to explore the impact of MG (<40 mmHg vs. >40 mmHg) in patients with AVAi <0.6 cm 2 /m 2 (PLG-SAS vs. HG-SAS) and to explore the impact of AVAi (<0.6 cm 2 /m 2 vs. >0.6 cm 2 /m 2 ) in patients with MG <40 mmHg (PLG-SAS vs MAS) we performed 2 different propensity score analyses. Patients were censored at the time of surgery. Results: Overall, during 23 [IQR, 10–47] months of follow-up 1003 patients died and 770 patients underwent aortic valve replacement. IPW-adjusted natural history was significantly better in patients with MAS, intermediate for patients with PLG-SAS and worst in patients with HG-SAS (59 vs. 47 vs. 41%, p<0.001, see Figure 1A). Furthermore, at equal MG (448 pairs), survival was significantly better in patients with MAS compared with PLG-SAS (54% vs. 39% p<0.001, see Figure 1B) and at equal AVAi (377 pairs), survival was significantly better in patients with PLG-SAS compared with HG-SAS (43% vs. 32% p<0.001, see Figure 1C). Conclusions: In this large multicentric cohort, survival of PLG-SAS patients was better than that of HG-SAS patients and worse than that of MAS patients. Furthermore, with a comparable mean gradient, the smaller the calculated AVAi, the worse the prognosis whereas with a comparable AVAi, the higher the mean gradient, the worse the prognosis. Taking together, these data demonstrate that PLG-SAS is an intermediate form in the disease continuum, HG-SAS being the most malignant form of AS. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Fonds National de la Recherche Scientifique (F.R.S.–FNRS)